Effectiveness of the “Genting” Application on Cadres’ Knowledge and Attitudes toward Child Stunting Screening in Bengkulu City - Andeka, Wisuda Andeka Marleni; Linda; Farida Halis; Heni Hendriyani; Reka Lagora Marsofely (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2025)
The prevalence of stunting in Indonesia increased from 18% in 2007 to 19.3% in 2018. However, Indonesia’s nutrition status survey showed that the stunting rate decreased from 24.4% in 2021 to 21.6% in 2022. The government has promoted technology-based strategies through digital applications that are widely accessible to the community. This study aimed to examine the effectiveness of the “Genting” application in improving the knowledge and attitudes of health cadres related to child stunting screening. The study employed a quantitative approach using a quasi-experimental design with two groups and pre-test and post-test measurements. The sample consisted of 70 respondents, which included 35 cadres in the intervention group and 35 cadres in the control group. All respondents were active posyandu cadres in Bengkulu City who were able to read, write, and operate Android-based applications. The analysis showed a statistically significant improvement in knowledge scores before and after the intervention in both groups (p < 0.05). The mean increase in knowledge scores was 1.19 points in the group that used the “Genting” application and 1.32 points in the group that used the other Android application. Analysis of attitude scores showed a statistically significant difference before and after the intervention in both groups (p < 0.05). The mean difference in attitude scores between the group that used the “Genting” application and the group that used the other Android application was 2.72 points. These findings indicate that the “Genting” application is effective in increasing knowledge and attitudes about stunting prevention in child cadres in Bengkulu City.